Gender differences in compliance: The role of social value orientation - Kerstin Grosch; Holger A. Rau (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
This paper experimentally analyzes the determinants of compliance in a cheating game. The results show that men are less compliant than women. We demonstrate that social value orientation predicts differences in cheating and explains the gender differences. Individualistic men cheat more than all social types of both gender.
Keywords: C91; H26; J16; 330; Experiment; Gender Differences; Honesty; Social Value Orientation